The contentious tax procedure in a Bicentennial Peru of the XXI century. Some commentaries and new technologies - Ezeta Carpio, Sergio (2021)
The article deals with the contentious tax procedure in Peru. After making a brief explanation of the current scheme, some problematic aspects that must be corrected or perfected in the legislation are highlighted, always with the purpose of providing a better service to the citizens who wants to have fast and efficient ways to exercise their right of defense and, linked to it, their right to contradict administrative acts (in this case, issued by the Tax Administration) that, in their understanding, improperly affect their property or rights in an undue manner.A current issue that is also discussed is the transition from the physical file to the electronic file, which has been advanced and is expected to be ready in the future. On this point, it is mentioned that due to the COVID-19 pandemic this process has been precipitated, although there had already been progress in this regard for several years. In addition, the connection between the electronic file and a more general issue, such as the digital government (or electronic government), is highlighted.